Food insecurity and the extremes of childhood weight: defining windows of vulnerability. (21st November 2019) - Zhu, Yeyi; Mangini, Lauren D; Hayward, Mark D; Forman, Michele R
Abstract: Background: Weight extremes and food insecurity (FIS) represent public-health challenges, yet their associations in childhood remain unclear. We aimed to investigate the longitudinal time-specific relationship between FIS and risk of overweight/obesity and underweight in kindergarten through 8th grade. Methods: In the prospective Early Childhood Longitudinal Study–Kindergarten Cohort (1998–2007) of 6368 children, household FIS was assessed by the validated US Household Food Security Survey Module in kindergarten, 3rd, 5th and 8th grades. Multivariable linear-regression and Poisson-regression models were computed. Results: Compared with children experiencing food security (FS), children exposed to FIS in 5th grade had 0.19 [95% confidence interval (CI): 0.07–0.30] and 0.17 (0.06–0.27) higher body mass index z-score (BMIZ) in the 5th and 8th grades, respectively, whereas FIS in the 8th grade was associated with a 0.29 (0.19–0.40) higher BMIZ at the same wave, after adjusting for covariates and FIS at earlier waves. Children with FIS vs FS had 27% (relative risk: 1.27, 95% CI: 1.07–1.51), 21% (1.21, 1.08–1.35) and 28% (1.28, 1.07–1.53) higher risk of overweight/obesity in the 3rd, 5th and 8th grades, respectively, adjusting for covariates and FIS at prior wave(s). Children with FIS vs FS in kindergarten had a 2.76-fold (1.22–6.25) higher risk of underweight in the 8th grade. Conclusions: Proximal exposure to household FIS was associated with a higher risk of overweight/obesity in the 3rd, 5th and 8th grades. FIS in kindergarten was associated with a risk of underweight in the 8th grade. Thus, FIS coexists in weight extremes during vulnerable early-life windows in the USA, similarly to the global burden of FIS.